The Impacts of Reducing the Infection Rate and Infection Source on the Transmission of Emerging Infectious Diseases - Jia-Tong Li (Discrete Dynamics in Nature and Society)
There are many prevention and control measures for emerging infectious diseases. This paper divides the effects of these measures into two categories. One is to reduce the infection rate. The other is to use diagnosis rate to reflect the decreases of the infection source. The impacts of measures intensity, diagnosis rate, and the start time of taking measures on emerging infectious diseases with infectious capacity during the incubation period are considered comprehensively by using a differential equation model. Results show that for each diagnosis rate, the number of infections and deaths has a phase change structure with respect to the measures intensity. If the measures intensity is less than the value of the phase change point, the epidemic will break out whenever measures are taken. If the measures intensity is greater than the value of the phase change point, the epidemic can be controlled when the measures are taken timely. But if measures are not taken in time, epidemic will also break out. The location of the phase change point is related to the diagnosis rate. For the different measures intensity and the diagnosis rate, this paper gives a method to judge whether the spread of the corresponding epidemic can be controlled.